SERCA inhibition improves lifespan and healthspan in a chemical model of Parkinson disease in Caenorhabditis elegans - Romero-Sanz, Silvia; Caldero-Escudero, Elena; Álvarez-Illera, Pilar; Santo-Domingo, Jaime; Fonteriz, Rosalba I.; Montero, Mayte; Álvarez, Javier (Frontiers in Pharmacology, 2023)
The high prevalence of neurodegenerative diseases in our population and the lack of effective treatments encourage the search for new therapeutic targets for these pathologies. We have recently described that submaximal inhibition of the Sarco-Endoplasmic Reticulum Ca2+ ATPase (SERCA), the main responsible for ER calcium storage, is able to increase lifespan in C. elegans worms by mechanisms involving mitochondrial metabolism and nutrient-sensitive pathways. We have studied here the effects of submaximal SERCA inhibition in a chemical model of Parkinson's disease (PD) induced in C. elegans worms by treatment with the mitochondrial complex I inhibitor rotenone. For specific SERCA inhibition, we treated worms with RNAi against sca-1, the sole orthologue of SERCA in C. elegans. Our results show that rotenone produces alterations in worms that include decreased lifespan, smaller size, reduced fertility, decreased motility, defecation and pumping rate, increased mitochondrial ROS production, reduced mitochondrial membrane potential and oxygen consumption rate, altered mitochondrial structure, and altered ethanol preference in behavioral studies. Most of these alterations were either fully or partially reversed in worms treated with sca-1 RNAi, suggesting that SERCA inhibition could be a novel pharmacological target in the prevention or treatment of neurodegeneration.